Echinometra sea urchins acclimatized to elevated pCO2 at volcanic vents outperform those under present‐day pCO2 conditions. (2nd May 2016) - Uthicke, Sven; Ebert, Thomas; Liddy, Michelle; Johansson, Charlotte; Fabricius, Katharina E.; Lamare, Miles
Abstract: Rising atmospheric CO2 concentrations will significantly reduce ocean pH during the 21st century (ocean acidification, OA). This may hamper calcification in marine organisms such as corals and echinoderms, as shown in many laboratory‐based experiments. Sea urchins are considered highly vulnerable to OA. We studied an Echinometra species on natural volcanic CO2 vents in Papua New Guinea, where they are CO2 ‐acclimatized and also subjected to secondary ecological changes from elevated CO2 . Near the vent site, the urchins experienced large daily variations in pH (>1 unit) and p CO2 (>2000 ppm) and average pH values (pHT 7.73) much below those expected under the most pessimistic future emission scenarios. Growth was measured over a 17‐month period using tetracycline tagging of the calcareous feeding lanterns. Average‐sized urchins grew more than twice as fast at the vent compared with those at an adjacent control site and assumed larger sizes at the vent compared to the control site and two other sites at another reef near‐by. A small reduction in gonad weight was detected at the vents, but no differences in mortality, respiration, or degree of test calcification were detected between urchins from vent and control populations. Thus, urchins did not only persist but actually 'thrived' under extreme CO2 conditions. We suggest an ecological basis for this response: Increased algal productivity under increased p CO2 provided more food at the vent, resulting in higher growth rates. The wider implication of our observation is that laboratory studies on non‐acclimatized specimens, which typically do not consider ecological changes, can lead to erroneous conclusions on responses to global change.